HAK WARIS ANAK LAKI-LAKI DAN PEREMPUAN DI NEGARA-NEGARA MUSLIM - Herdiansa, Herdiansa; Fauzizah, Siti (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Conflicts between heirs are often caused by the desire to get an excess portion, which creates a sense of injustice and can lead to conflict. This has been proven by the high demand for mediation and lawsuits regarding inheritance in Indonesian religious courts. This research aims to answer questions related to regulations regarding the distribution of inheritance between male and female children in Muslim countries, including Indonesia. The type of research used in this research is normative juridical research (doctrinal legal research) and uses the form of library study research, by reviewing literature that is relevant to the theme being discussed. This research is descriptive-comparative in nature by explaining legal regulations and comparing inheritance rights for sons and daughters in Muslim countries. The results of this research are that the concept of Li Az-Zakari Mitslu Hazzi al Untsayain the Qur'an has become a permanent guideline in the division of inheritance, so that the regulation of 2:1 distribution of inheritance between sons and daughters is widely implemented by Muslim countries. such as Indonesia, Malaysia, Egypt, Morocco, Jordan and Tunisia. Several Muslim countries tend to maintain the provisions in faraid law regarding inheritance distribution. This is different from the distribution of inheritance in Turkey where the ratio of inheritance between sons and daughters is 1:1. The comparison of inheritance in Turkey is influenced by the factor of equal rights between men and women regarding inheritance rights.